Perancangan Sistem e-Library Berbasis Web Jurusan Teknik Elektro Politeknik Negeri Padang - Nasrul - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
Data communication technology allows the building of a network of computers with online applications. With the Padang State Polytechnic library system that still uses a manual system in the form of books and cards – cards that contain data – data book is considered not efficient anymore, so it takes a library of WEB - based information systems. With the utilization of internet technology in tended for delivery and the need for rapid information retrieval, facilitate student and informed the user in the title of books desired, assist the Polytechnic library Country Meadow in logging the books, because of the internet as a very broad network is an effective and efficient means for this application.